Student training program of building drawing and augmented reality in SMKN 2 Pangkalpinang - Maulana Arif; Yudistira Bagus Pratama (Universitas Muhammadiyah Magelang, 2023)
SMK Negeri 2 Pangkalpinang is a public vocational high school in Pangkalpinang, which has a Construction and Property Technology Program and a Computer and Informatics Engineering Program. To support the improvement of the hard skills of the students, implementing a training program is one way that is quite solutive. The student training program is devoted to building drawing technique training for the Building Modeling and Information Design Department, which hones students' drawing skills. In addition, the students are also given training related to augmented reality for the Multimedia Department. This activity also produced works in the form of design building drawings and augmented reality products.